‘Ted Cruz cucks again’: The insult term cuck as an alt-right masculinist signifier - Kosse, Maureen (Gender and Language, 2022)
This article provides a multimodal semiotic analysis of the word cuck as used in online white supremacist spaces. A fundamental belief of the white supremacist ‘alt-right’ movement is an anti-Semitic narrative that positions Jewish people as a ‘global elite’ that seeks to oppress and eliminate white populations. Central to this belief is that Jewish people actively manipulate populations of colour, Black people in particular, to overtake white populations in a process known as ‘white genocide’ or ‘the great replacement’. Based on a digital ethnography of alt-right communities on Voat, Twitter and Reddit, this article demonstrates how the memeified word ‘cuck’, a pejorative term for ‘weak’ men on the US political right wing, draws from and reproduces this white nationalist conspiracy theory through allusions to interracial cuckold pornography. While disguised as innocuous, expressions like ‘cuck’ provide insight into how the alt-right weaponises misogynist and racist humour in its radicalisation efforts.